(untitled) - Riitta Turjamaa; Johanna Simon-Bellamy; Leena Salminen; Eliisa Löyttyniemi; Satu Kajander-Unkuri (Central European Journal of Nursing and Midwifery, 2022)
Aim: To describe graduating nursing students' competence based on their knowledge in the nursing of a patient with acute coronary syndrome (ACS) and their self-assessed nurse competence. Design: A cross-sectional survey. Methods: The data were collected from 2018-2019 using an ACS test developed for this study and using the Nurse Competence Scale. The sample contained 47 graduating nursing students. The statistical analysis methods were used. Results: Only 48.9% (n = 23) of the students scored an accepted level of knowledge in the nursing of a patient with ACS, and a little over half (51.1%; n = 24) failed the ACS test. Graduating nursing students' self-assessed nurse competence was at a good level (69.7; VAS 0-100). No statistically significant differences in nurse competence assessments occurred between students who passed the ACS test and those who failed it. Conclusion: While graduating nursing students have a good level of nursing competence, their knowledge in the nursing of a patient with ACS was poor. It is important to emphasize the nursing of a patient with ACS in nursing education and to pay especially close attention to interpreting the patient's electrocardiogram findings.